VEGETABLE AND FRUIT CONSUMPTION PATTERNS, SPORTS ACTIVITIES AND PHYSICAL FITNESS LEVELS OF STUDENTS IN SMP NEGERI 3 MENGWI SUB-DISTRICT MENGWI DISTRICTS BADUNG - Fransiska Kadek Desi Asri; I Wayan Ambartana; I Made Suarjana (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2020)
In Bali, lack of fruit and vegetable consumption in adolescents reaches 97,5%. This study aims to determine the pattern of vegetable and fruit consumption, sports activities and the level of fitness of students in SMP Negeri 3. This research was conducted at Mengwi Badung State Middle School 3 in May 2019. This type of research was observational with a cross sectional design, the population in this study were all eighth grade students. The number of samples is 88 samples. Data on physical fitness levels were collected by carrying out two fitness tests namely a 50 meter fast run and 60 seconds sit-ups. The consumption pattern data is collected by conducting interviews using the SQ-FFQ form. Sports activity data was collected by filling out questionnaires directly by the sample. The results of this study are known to be the majority of the sample (77.3%) including the type of consumption of less vegetables, the frequency of sample vegetable consumption was mostly (38.6%) less, and the amount of consumption of vegetable samples (100%) is less. Most types of fruit consumption (84.1%) are sufficient, the frequency of sample fruit consumption was mostly (51.1%) good, and the amount of consumption of sample fruit was mostly (76.1%) less. The sample sports activities were mostly (52.3%) moderate. The sample physical fitness level was mostly (81.8%) good. There was no trend between the type, frequency, and amount of vegetable consumption with physical fitness. There was no tendency between the type, frequency, and amount of fruit consumption with physical fitness. There is a tendency between sports activities with physical fitness levels.Keywords: Vegetable Consumption, Fruit, Sports Activities, Physical Fitness